Boosting Catalytic Activity by Seeding Nanocatalysts onto Interlayers to Inhibit Polysulfide Shuttling in Li–S Batteries. (25th April 2021) - Xia, Jingyi; Hua, Wuxing; Wang, Li; Sun, Yafei; Geng, Chuannan; Zhang, Chen; Wang, Weichao; Wan, Ying; Yang, Quan‐Hong
Abstract: The shuttling of soluble lithium polysulfides (LiPSs) is one of the main bottlenecks to the practical use of Li–S batteries. It is reported that in situ synthesized ultrasmall vanadium nitride nanoparticles dispersed on porous nitrogen‐doped graphene (denoted VN@NG) as a catalytic interlayer solves this problem. The ultrasmall size of VN particles provide ample triple‐phase interfaces (the reactive interfaces among VN nanocatalyst, NG conductive substrate, and electrolyte) for accelerating LiPS conversion and Li2 S deposition, which greatly reduces the accumulation of LiPSs in the electrolyte and therefore inhibits the shuttle effect. Their high catalytic activity is confirmed by a reduced activation energy of the Li2 S4 conversion step based on temperature‐dependent cyclic voltammetric (CV) measurements and the reduced shuttle effect is detected by in situ Raman spectra. With the VN nanocatalyst, Li–S batteries have an outstanding cycling performance with a low capacity decay rate of 0.075% per cycle over 500 cycles at 2 C. A high capacity retention of 84.5% over 200 cycles at 0.2 C is achieved with a high sulfur loading of 7.3 mg cm −2 . Abstract : A catalytic interlayer assembled with the in situ synthesized vanadium nitride (VN) nanocatalysts is highly effective to suppress the shuttle effect and enhance the cyclic stability of Li–S batteries. The uniformly dispersed VN nanocatalysts present superior catalytic activity, which can dramatically accelerate the conversion of the polysulfides and the Li2 S nucleation and growth.